The Impact of the US Dollar's Volatility on Taiwanese Economy - A Case of Export-led Growth - Fu, Janice (2005)
According to the trading records over decades, Taiwanese economy seems to be long dependent on the U.S. market and hence it is suggested that exchange rate uncertainty has a long-term effect on exports. The proxy of volatility in this study is measured using three techniques including the GARCH (1,1) procedure, the ordinary moving average method and a moving average standard deviation approach. The real exchange rate is employed throughout the study in order to reflect the property of the exchange rate over time. A striking result is found in this study.